Isolation and Characterization of Nanofibrillar Cellulose from Agave tequilana Weber Bagasse - Hasbleidy Palacios Hinestroza; Javier A. Hernández Diaz; Marianelly Esquivel Alfaro; Guillermo Toriz; Orlando J. Rojas; Belkis C. Sulbarán-Rangel (Advances in Materials Science and Engineering)
The bagasse of Agave tequilana Weber is one of the most abundant agroindustrial wastes in the state of Jalisco. However, at the present time, there is no technical use for this waste, and its high availability makes it an environmental problem. The objective of this research was to take advantage of this waste and give it an added value to be used in the elaboration of advanced materials. In this sense, the agave bagasse cellulose was obtained using an organosolv method. To obtain the nanofibrils, the cellulose was passed through 6 cycles of a microfluidizer. The material was classified by FTIR, confirming the presence of the functional groups (O-H, C-H, C-C, and C-O-C), characteristics of cellulose, and the elimination of hemicellulose and lignin present in agave bagasse without treatment. The X-ray diffraction technique allowed the determination of the degree of crystallinity of the cellulose nanofibers, which was 68.5%, with a negative zeta potential of −42 mV. The images from the atomic force microscopy helped for the observation of the degree of fibrillation in the cellulose, and with the software ImageJ, the average diameter of the nanofibers was determined to be 75 ± 5 nm with a relatively uniform length of 1.0–1.2 μm. Finally, by means of thermogravimetric analysis, it was found that the obtained cellulose nanofibers (CNFs) supported high temperatures of thermal decomposition, so it was concluded that due to the diameter of the fibrils, the high resistance to pressure, and elasticity, the nanofibrils obtained in this investigation can be used in the elaboration of advanced materials.